Research on Protein Thermal Condensation Detection Based on Phase Modulation SPR Imaging - Yang Zi Kang (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
The existing of labeling methods can not completely meet the requirements of protein detection. It is currently in urgent need of sensitive, labeless, real-time and high throughput protein detection methods. A novel SPR imaging biomolecular interatction detection method based on time domain phase modulation is presented in this thesis. Experimental apparatus of SPR imaging biomolecular interaction detection based on TDPM is established. Biomolecular interaction is detected. 2×2 lysozyme array chip is prepared and lysozyme thermal condensation is detected by the experimental apparatus. SPR curves of the interaction are obtained and kinetic parameters are calculated. It can sensitively acquire real-time phase change caused by biomolecular interaction based on interference imaging, and resolve related bioinformation, which is a potential tool for proteomics research.